Typology of Structural and Semantic Organization of Phraseological Units in the Segment with its Concentrated Implication in the Prose by M.A Sholokhov (Proceedings of Southern Federal University. Philology, 2020)
The artistic prose of M. A. Sholokhov is characterized by a large number of phraseological locutions, their concentrated use in the text, as well as non-trivial compatibility of phraseological locutions among themselves. Concentrated used phraseological locutions make in units. Differences in the structural and semantic organization of them in the unit are the basis for their typology.By similarity / difference of the structural organization of phraseological locutions in the unit there are similar structural phraseological units, phraseological locutions with different structure, and locutions that are members of the same phraseological nest.According to the type of paradigmatic relations between phraseological locutions synonymic, antonymic, hyper-hyponymic and syncretic units of phraseological locutions are distinguished in the unit.The number of phraseological units in a block can vary from two to five (sometimes more). In the text of a complex syntactic whole phraseological units can be located contact or distant. By syntactic organization units of phraseological locutions with common conjugation relations and phraseological units with complex syntactic organization are distinguished.Due to the concentrated use of phraseological locutions, the writer intensifies the imagery and expressiveness of phraseological locutions, actualizes certain semes of meanings, increases their aesthetic value.Key words: concentrated use, unit of phraseological locutions, imagery, expressiveness of phraseological locutionsDOI 10.18522/1995-0640-2020-3-12-21